CERITA PENDEK DALAM PEMBELAJARAN MEMBACA SISWA SMA KELAS XI (SEBUAH USULAN) - PARE, ALSIN (LATERNE, 2016)
The research with the title "short stories in read learning " aims to describe the usage of short stories in read learning of German language for high school students of class XI. This study was conducted to determine the usage of short stories in read learning.   This research is qualitative descriptive type which describes the usage of short stories in learning German language. This research is based on the theory of the selection of short stories by Sutawijaya. In this theory sutawijaya said that there are two criteria of choosing stories rhe first one is legibility criteria that include clarity of language, clarity of theme, the simplicity of the plot, the simplicityof character, the simplicity of backdrop, the clarity of central narrative, and the second one is suitability criteria that include curriculum. From the theory of selection of short story then arranged researcher of learning to read by using short stories that have been selected and analyzed.                                   The result is a creative design of learning to read by using short stories that encourage students to understand the short story by using their senses. And the conclusion is a lesson plan by use short stories can be applied by a teacher in the high school students of class XI. Then in terms of the selection of short stories selected short stories titled "Tante Anna" by Karl-Heinz Ganser had met the criteria of legibility but do not meet the criteria of suitability. Key words: short stories, learning, read